Development Of Residential Energy Harvesting System With Arduino Application - Mohd Noh, Mohd Syahrin Amri; Wagiman, Mohammad Ikhwan Shah; Kadmin, Ahmad Fauzan; Zakaria, Zahriladha (Penerbit Universiti, UTeM, 2019)
The common electricity source is currently being generated through solar panel, wind turbine and hydroelectric. However, these methods require high cost and large space for the system operation. This paper proposed a Pico hydro free charging system from high pressure water of the home piping system stored to power bank for home lighting application. The usage of small-scale turbine in the system generated electricity to continuous charging the power bank. The power bank then acted as a free power source used to light up a 5V LED bulb as a free lighting source. The additional usage of Arduino helped to provide the information display on the generated current, voltage and the water flow rate. The piping size and length were evaluated and it was found that they significantly affected the voltage performance with the help of Arduino application for monitoring purpose. The uniqueness of this project is that it can be operated with a minimum water pressure of 15 Psi to generate renewable energy storage from incoming housing piping system.